We are given the system of equations -:
![\large{ \begin{cases} 2x + 3y = - 14 \\ y = 6x + 22 \end{cases}}](https://tex.z-dn.net/?f=%20%5Clarge%7B%20%5Cbegin%7Bcases%7D%202x%20%2B%203y%20%3D%20%20-%2014%20%5C%5C%20y%20%3D%206x%20%2B%2022%20%5Cend%7Bcases%7D%7D)
Since the second equation is y-isolated equation. It can be substituted as y = 6x+22 in the first equation.
![\large{2x + 3(6x + 22) = - 14}](https://tex.z-dn.net/?f=%20%5Clarge%7B2x%20%2B%203%286x%20%2B%2022%29%20%3D%20%20-%2014%7D)
Expand 3 in the expression so we can combine like terms and isolate x-variable.
![\large{2x + 18x + 66 = - 14}](https://tex.z-dn.net/?f=%20%5Clarge%7B2x%20%2B%2018x%20%2B%2066%20%3D%20%20-%2014%7D)
Then combine like terms.
![\large{20x + 66 = - 14}](https://tex.z-dn.net/?f=%20%5Clarge%7B20x%20%2B%2066%20%3D%20%20-%2014%7D)
Get rid of 66 from the left side by subtracting both sides by itself.
![\large{20x + 66 - 66 = - 14 - 66} \\ \large{20x = - 80}](https://tex.z-dn.net/?f=%20%5Clarge%7B20x%20%2B%2066%20-%2066%20%3D%20%20-%2014%20-%2066%7D%20%5C%5C%20%20%5Clarge%7B20x%20%3D%20%20-%2080%7D)
To finally isolate the variable, divide both sides by 20 so we can leave x only on the left side.
![\large{ \frac{20x}{20} = \frac{ - 80}{20} }](https://tex.z-dn.net/?f=%20%5Clarge%7B%20%5Cfrac%7B20x%7D%7B20%7D%20%20%3D%20%20%5Cfrac%7B%20-%2080%7D%7B20%7D%20%7D)
Simplify to the simplest form.
![\large{x = - 4}](https://tex.z-dn.net/?f=%20%5Clarge%7Bx%20%3D%20%20-%204%7D)
Normally, we have to find the y-value too but since we only find x-value. The answer is x = -4.
Answer
I hope this helps! If you have any questions or doubts regarding my answer, explanation or system of equations, feel free to ask!